The role of digital technology in empowering children for sustainable development. - Faiza TOUNSI (Social Empowerment Journal, 2019)
"Digital transformation" has already changed the world. Technology is now accessible to all members of society and has made life easier, faster and more prosperous. It has also reached all age groups of males and females. One of the advantages of these digital technologies is that they may change the rules of the game for children who are left behind - whether because of poverty, race, ethnicity, gender, disability, displacement or geographical isolation - and allow them to be linked to a world of opportunity, and Providing them with the skills they need to succeed in a digital world, but unless access is expanded, digital technology may create a new divide that prevents children from realizing their potential. And the risks to which the child may be exposed Even more vulnerable to exploitation in various aspects as a result of digital literacy so deliberately many countries and including Algeria to the positive discrimination of the child to protect it from the damage caused by the digital world to enable him and the advancement of society and keep up with technological development and by focusing on investment in the field of digital technology